Tunisia in a Changing Climate: Assessment and Actions for Increased Resilience and Development - Verner, Dorte (World Bank, 2015)
This book provides an assessment of climate risks, opportunities and possible actions in Tunisia. It recognizes that the Tunisian revolution of January 14th 2011 has created significant change in Tunisia resulting in new challenges and opportunities for addressing climate change. Following the revolution access to information, improved institutions and accountability may enhance governance and transparency essential for effective climate change responses however political uncertainty has affected both foreign direct investment and tourism impacting already high rates of poverty and unemployment. Chapter 1 highlights that climate change is already damaging people's livelihoods and well-being in Tunisia and without action climate change will deepen the already significant poverty and unemployment in the country and may unravel the development gains made in recent decades contributing to food insecurity and political instability. Chapter 2 provides a synthesis of evidence of climate variability and change in Tunisia by tracking past climate trends and presenting a range of plausible climate change scenarios. It also illustrates statistical downscaling techniques as a means of repairing meteorological data sets and assessing sensitivity to local climate change. Using the evidence to date it summaries potential impacts and uncertainties associated with climate change that may affect Tunisia's water, land, agriculture, and coastal zone management. Chapter 3 provides a detailed quantitative analysis of the current and likely future impacts of climate change on GDP and household incomes. The analyses take into account global climate change and international food prices. Chapter 4 addresses the local impacts of climate change focusing in particular at seven governorates in the South and Centre that are particularly dependent on climate sensitive sectors such as agriculture and has high rates of unemployment. The analyses are based on qualitative field research. Chapter 5 provides policy recommendations for Tunisia in line with the World Bank?s Interim Strategy Note for the country focused on building climate resilience through economic diversification, renewed sustainable growth and job creation, as well as the promotion of social and economic inclusion by improving access to basic services for underserved communities and improving the efficiency of social safety net programs. Strong coordinated governance and improved access to climate related information and enhanced climate related human and technical skill development are critical factors to enable climate change action.